Youth confidence in the quality of public transport services: the case of greater KL, Malaysia - Dahalan, Dzuhailmi; D’Silva, Jeffrey Lawrence; Abdullah, Haslinda; Ismail, Ismi Arif; Ahmad, Nobaya (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Developing an efficient public transportation system is an on-going challenge in many developing countries including a middle income country such as Malaysia. This study analyses the confidence level of youths in the quality of public transport services in the Klang Valley (Greater KL). Primary data were collected from a field questionnaire survey of 445 Klang Valley youths who were frequent users of public transportation in the area. It was found that although the majority of the respondents were frequent users of public transportation their level of confidence in the quality of public transportation service provided by the operators was only moderate. Most of them, nevertheless, acknowledged the importance of public transportation in their daily life but stressed on the imperative of upgrading the service quality of the system so as to enhance their confidence level in it.